Risk Factors for Fracture in Diabetes: The Canadian Multicentre Osteoporosis Study. (2nd December 2013) - Fraser, Lisa-Ann; Papaioannou, Alexandra; Adachi, Jonathan D.; Ma, Jinhui; Thabane, Lehana
Abstract : Objective . Individuals with diabetes have been found to be at increased risk of nontraumatic fracture. However, within the diabetic population, how to distinguish who is at the highest risk and warranting therapy has remained elusive. Design . Cross-sectional analysis of a national population-based cohort study. Patients . Men and women over the age of 50 with diabetes from across Canada. Measurements . Logistic regression analysis to identify diabetes specific factors associated with a history of one or more non-traumatic fractures. Results . Six hundred and six individuals with diabetes with a mean age of 69 years were examined. Thirty percent had a history of non-traumatic fracture. Macrovascular diseases in the form of stroke or TIA, as well as hypertension, were found to be independently associated with fragility fracture. Other, more traditional, clinical risk factors were also associated with fracture, including increased age, female gender, rheumatoid arthritis, family history of osteoporosis, and decreased bone mineral density. Conclusions . In this cohort of Canadians with diabetes, those with rheumatoid arthritis, a family history of osteoporosis, female gender, increased age, decreased BMD, cerebrovascular disease, or hypertension were more likely to have had a non-traumatic fracture. These risk factors may be important to clinicians when identifying which of their diabetic patients are at highest risk of fracture and in need of preventative therapies.